(untitled) (Global Journal of Science Frontier Research, 2012)
New magnesium lead borate glasses (10-x) MgO-xMgCl2-40PbO-50B2O3 (x = 0, 1, 2, 3, 4, 5, 6, 7, 8, and 10 mole%) were prepared by melt quenching technique. Fourier transform infrared spectroscopic studies revealed the presence of BO3 trigonal and BO4 tetrahedral structural units in these glasses. The optical energy band gaps, Urbach energies and theoretical refractive index values are reported. No considerable structural changes with the composition are observed. FTIR revealed the formation of NBOs and the behaviour of MgO as glass network modifier. The expansion of B-O network with increasing x mole% is attributed to the presence of Chlorine ions.